EVALUATING THE IMPACT OF SCHOOL-BASED ENGLISH CLUBS ON ENGLISH LANGUAGE ACQUISITION AND LEARNERS' SELF-CONFIDENCE - Pratiwi, Widya Rizky (Journal of Research on Language Education, 2024)
This research investigates the impact of school-based English clubs on language skill development among Indonesian high school students, addressing the educational gap in English proficiency as an impact of globalization. Utilizing a qualitative case study design, the study engaged 21 active members of a combined English club at Benteng Rotterdam, Makassar, employing online questionnaires and focus group discussions to gather data on participants' experiences and challenges. Findings reveal that participation in English clubs significantly enhances students' speaking, listening, and reading skills, with 81% of students reporting increased confidence in speaking. However, challenges such as inconsistent program implementation, pronunciation difficulties, and limited vocabulary retention were identified. This study contributes to the understanding of extracurricular language learning by highlighting the effectiveness of English clubs and offering recommendations for improving their implementation. Insights gained from this research can inform educators and policymakers in designing more effective language learning environments that support students’ needs and foster equitable access to language education.